Profil Kemamampuan Berpikir Kreatif dalam Pemecahan Masalah Matematika pada Gaya Kognitif Reflektif dan Impulsif - Miswati, Vina Dyah; Sugiyanti, Sugiyanti; Pramasdyahsari, Agnita Siska (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
This study aims to describe the profile of students' mathematical creative thinking ability in solving math problems of material circles students on with reflective and impulsive cognitive styles. This type of research is qualitative descriptive research. The subjects taken were 2 grade VIII students at one of the Madrasah Tsanawiyah in Magelang even semester of the 2020/2021 school year, each of which was cognitively reflective and cognitively impulsive. Data collection is used with MFFT test, mathematical creative thinking test and interview. Data analysis techniques are carried out in 3 stages, namely data reduction, data presentation, conclusion drawing. The technique of checking the validity of data using triangulation method is to compare the results of the test understanding mathematical concepts with the results of interviews. The analysis was developed based on indicators of creative thinking by paying attention to the cognitive style. Based on the results of the analysis, it is known that subjects with reflective cognitive styles have a category of TKBK 3 which means creative because it is able to meet only 2 indicators of fluency and flexibility. Subjects with impulsive cognitive style have a category of TKBK 1 which means less creative because the subject only meets 1 indicator, namely fluency.